3x-7y+6z=5

Simple and best practice solution for 3x-7y+6z=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-7y+6z=5 equation:


Simplifying
3x + -7y + 6z = 5

Solving
3x + -7y + 6z = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7y' to each side of the equation.
3x + -7y + 7y + 6z = 5 + 7y

Combine like terms: -7y + 7y = 0
3x + 0 + 6z = 5 + 7y
3x + 6z = 5 + 7y

Add '-6z' to each side of the equation.
3x + 6z + -6z = 5 + 7y + -6z

Combine like terms: 6z + -6z = 0
3x + 0 = 5 + 7y + -6z
3x = 5 + 7y + -6z

Divide each side by '3'.
x = 1.666666667 + 2.333333333y + -2z

Simplifying
x = 1.666666667 + 2.333333333y + -2z

See similar equations:

| X^8=1/12 | | 16/5x=1/10 | | x-5y=-2 | | 9=2w+5 | | -8n-3=-27 | | 3(3x-3)-28=4x-2 | | 3/2*(1-4x)^1/2=-30 | | (((3x-1/4)^2))^4 | | 5x-12=10-6x | | FxD=F | | 11/2*31/2*23/4 | | 4=-6+x | | A+C=A | | 6+9=3x | | -30=3r | | 38=7b+10 | | 2(x-1)=10(1-x)+6 | | 3xy+4xy-xy= | | 4x+29=5-8(x+6) | | 25x^2-36=o | | 6(5y-1)=-2y-38 | | 2+4r=5+4r | | X*7-4x=19-2x | | 90=-6(1+8q) | | 1-5m+3m=3 | | -x^3-6x^2+36x+216=0 | | -8-3(w+13)=4(w+11)-7w | | 15=5/6c | | -2(3x+1)-6x+7= | | 3x-2=55 | | 3/4(x-1)=7/4 | | (1-k)X^2-2(1+k)X+3(k+1)=0 |

Equations solver categories